2020
DOI: 10.1042/bsr20200232
|View full text |Cite
|
Sign up to set email alerts
|

Statin use and the prognosis of patients with hepatocellular carcinoma: a meta-analysis

Abstract: Background: Association between statin use and prognosis in patients with hepatocellular carcinoma (HCC) remains unknown. We performed a meta-analysis of follow-up studies to systematically evaluate the influence of statin use on clinical outcome in HCC patients. Methods: Studies were obtained via systematic search of PubMed, Cochrane’s Library, and Embase databases. A randomized-effect model was used to pool the results. Subgroup analyses were performed to evaluate the influence of study charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 33 publications
2
16
0
Order By: Relevance
“…In this study, we also observed that statin use was associated with a lower incidence of tumor recurrence in patients with HBV-related HCC after curative resection (HR, 0.236), although not significant in the multivariate Liver Cancer 2022;11:22-37 DOI: 10.1159/000518940 analysis. This result is similar with our recently published study [46] and a meta-analysis [47], which showed that statin use was associated with reduced tumor recurrence in the HCC patients after curative resection. However, the proportions of patients taking statins were relatively small and all of the studies were retrospective; thus, numerous confounding factors could not be totally adjusted for.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, we also observed that statin use was associated with a lower incidence of tumor recurrence in patients with HBV-related HCC after curative resection (HR, 0.236), although not significant in the multivariate Liver Cancer 2022;11:22-37 DOI: 10.1159/000518940 analysis. This result is similar with our recently published study [46] and a meta-analysis [47], which showed that statin use was associated with reduced tumor recurrence in the HCC patients after curative resection. However, the proportions of patients taking statins were relatively small and all of the studies were retrospective; thus, numerous confounding factors could not be totally adjusted for.…”
Section: Discussionsupporting
confidence: 92%
“…With the technological advances in diagnostic methods in the past decade, the incidence of HCC has continued to increase [ 4 ]. Despite the use of multidisciplinary synthetic therapy after hepatectomy, HCC cells can escape these cancer therapeutics, leading to cancer recurrence, metastasis, and, eventually, death [ 5 ]. HCC has a poor prognosis, with a median survival of approximately 12 months [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the use of multidisciplinary synthetic therapy after hepatectomy, HCC cells can escape these cancer therapeutics, leading to cancer recurrence, metastasis, and, eventually, death [ 5 ]. HCC has a poor prognosis, with a median survival of approximately 12 months [ 5 ]. These data demonstrate the need of a reliable signature for tumor classification and prognosis to facilitate the planning of the therapeutic strategy in patients with HCC.…”
Section: Introductionmentioning
confidence: 99%
“…Another important potential confounding variable is statins, which are widely used globally to treat hypercholesterolemia and have become mainstays for the prevention of cardiovascular diseases. ( 4 ) Moreover, the anticancer effect of statins has been profoundly recognized. ( 5 ) Recently, a meta‐analysis showed that statin use was associated with reduced HCC‐related mortality in the overall patient population and HCC recurrence in patients after curative therapies.…”
mentioning
confidence: 99%
“…( 5 ) Recently, a meta‐analysis showed that statin use was associated with reduced HCC‐related mortality in the overall patient population and HCC recurrence in patients after curative therapies. ( 4 ) Meanwhile, its clinical applications are also under extensive investigation, including several clinical trials for the treatment of HCC (NCT01418729, NCT03275376, and NCT01903694, etc.) and prevention of HCC recurrence after curative treatment (NCT03024684, NCT03490461, and NCT03219372, etc.).…”
mentioning
confidence: 99%